Locating the Study of Religion in a Theory of the Academy: The Unexamined Relationship between Jonathan Z. Smith's Two Careers - Woll, Donald Bruce (Method & theory in the study of religion, 2019)
The central claim of this article is that Jonathan Z. Smith, in addition to his extensive contributions to the study of religion, makes a valuable contribution to the theory and responsible public exercise of cognitive power. This larger public concern is explicitly and repeatedly addressed in his writings on the academy in which he develops a theory of the academy that articulates the conditions essential to the responsible exercise of cognitive power. A further claim is that this theory constitutes the integrating standpoint of his study of religion. The failure to recognize the relationship between his theoretical writings on the academy and his study of religion, reflecting his two careers, has given rise to misunderstandings that have obscured the wider public significance of his entire oeuvre.